The impact strength of composite with Abaća (Musa textilis) fiber - Muhammad Alif Akbar; Heni Hendaryati; Mohamad Irkham Mamungkas (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2022)
Materials are growing day by day, one of the most widely used materials is composite material, a composite is a material formed from a mixture of two or more forming materials through an inhomogeneous mixture, where the mechanical properties of each forming material are different. The focus of this research is to utilize abaca fiber to be used as a composite material using a polyester matrix. The manufacturing method used is the vacuum infusion method. The purpose of this study was to determine the impact strength of composites with chopped and intact banana fiber filler with a weight fraction of 10%, 20% and 30%. The highest impact value in this study obtained an average impact value of 0.523 Joule/mm2 at 30% weight fraction variation with chopped fiber, while the lowest value got an average impact value of 0.071 Joule/mm2 at 30% weight fraction with intact fiber. This shows that the 2 variations in weight and shape of the fiber with abaca fiber filler based on this research affect the value of impact strength.